The effect of cyclic tensile loading on the stress-induced transformation mechanism in superelastic NiTi alloys: an in-situ X-ray diffraction study. (15th April 2015) - Polatidis, E.; Zotov, N.; Bischoff, E.; Mittemeijer, E.J.
Abstract : The effect of cyclic tensile loading on the transformation behavior of superelastic NiTi was investigated by in-situ synchrotron X-ray diffraction (XRD) and transmission electron microscopy (TEM). It was quantitatively demonstrated that cyclic tensile loading alters the reversible austenite–martensite transformation character from localized (transformation fronts propagating) to uniform. TEM and XRD showed that the change of transformation behavior is not related to the presence of retained martensite or a change in texture upon tensile load-cycling but to the introduction of dislocations.